Connection and Application of Logic In The Field Artificial Intelligence - Gunawan, Nisa Alawiyah; Salafi, Mufti; Nurfadilah, Ai Nurahma Lisva (Etunas Sukses Sistem, 2022)
This paper discusses the connection and implementation of logic as one of the sub-fields of discrete mathematics within other fields of informatics, namely artificial intelligence or artificial intelligence (artificial intelligence). The discussion is preceded by an introduction in the form of the definition of the field of artificial intelligence that we will review is also equipped with history and research discussion of other fields under the field of artificial intelligence. Next, we will discuss the relationship between logic and artificial intelligence. On the way will a new discussion emerges, namely the representation of knowledge as the basis for the construction of a logical system complex. In addition, in discussing the implementation of logic in our artificial intelligence field requires good reasoning. So here will also be explained the definition of various type of reasoning.